Effect of Return on Asset, Return on Equity, Debt to Equity Ratio to Return Stock Company Property and Real Estate In Indonesia Stock Exchange - Yuli Chomsatu Samrotun, Febriyansyah Lukmana Putra, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to determine the effect of Return on Assets, Return onEquity and Debt to Equity Ratio on stock returns Property and Real Estatein the Indonesian Stock Exchange. The sample used in this study as many as29 companies Property and Real Estate in Indonesia Stock Exchange period2012 - 2016. The technique of sampling using purposive sampling method.Testing the hypothesis in this study using multiple regression analysis.Results shows simultaneously throughout the study variables affect thestock returns, while partially 1) Return on Assets no effect on stock returns,2) Return on Equity effect on stock returns, 3) Debt to Equity Ratio has noeffect on stock returns.Keywords: ROA, ROE, DER and stock returns